2008
DOI: 10.1111/j.1572-0241.2008.02021.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amitriptyline on Gastric Sensorimotor Function and Postprandial Symptoms in Healthy Individuals: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: BACKGROUND Low-dose tricyclic antidepressants have been used to treat chronic somatic and gastrointestinal pain disorders, including refractory functional dyspepsia. However, there are only limited data on the effects of these drugs on upper gastrointestinal function. AIM To compare the effects of two doses of amitriptyline (AMT) and placebo on gastric accommodation, emptying, satiation, and postprandial symptoms in healthy volunteers. METHODS Using a parallel-group, double-blind, placebo-controlled design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 58 publications
4
36
0
Order By: Relevance
“…This was in agreement with a previous study in which a TCA, amitriptyline, slowed gastric solid emptying at 2 and 4 h in healthy volunteers (2). However, another study reported that mianserin, a tetracyclic antidepressant, did not affect solid or liquid gastric emptying (14).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This was in agreement with a previous study in which a TCA, amitriptyline, slowed gastric solid emptying at 2 and 4 h in healthy volunteers (2). However, another study reported that mianserin, a tetracyclic antidepressant, did not affect solid or liquid gastric emptying (14).…”
Section: Discussionsupporting
confidence: 81%
“…Antidepressants are widely prescribed in patients with FD in clinic (12,33,38). These drugs may modulate several aspects in FD such as improving psychiatric and psychological conditions, influencing central regulation of visceral pain stimuli, and modifying gut sensorimotor function (2)(3)(4). In previous studies, tricyclic antidepressants (TCAs) and selective serotonin reuptake inhibitors (SSRIs) were used to treat FD (21,37,43).…”
mentioning
confidence: 99%
“…Second, antidepressants have central analgesic actions and alter central processing of visceral pain stimuli (10, 27). Third, antidepressants may have local pharmacological actions on the gut and modulate gut sensorimotor functions (3,8,9).Desvenlafaxine succinate (DVS; Pristiq) is a new antidepressant, the third serotonin-norepinephrine reuptake inhibitor (SNRI) approved by the U.S. Food and Drug Administration for the treatment of major depressive disorders in 2008 (26, 35). It is a novel salt form of the isolated major active metabolite of the antidepressant venlafaxine.…”
mentioning
confidence: 99%
“…Second, antidepressants have central analgesic actions and alter central processing of visceral pain stimuli (10,27). Third, antidepressants may have local pharmacological actions on the gut and modulate gut sensorimotor functions (3,8,9).…”
mentioning
confidence: 99%
“…Known prokinetic medications include metoclopramide, domperidone, erythromycin and cholinergic medications such as bethanechol [14][15][16][17][18][19][20]. Medications known to slow gastric emptying include opioid narcotics, tramadol, tricyclic antidepressants, calcium channel blockers, dopamine agonists, octreotide, anticholinergics, clonidine, and phenothiazines [14,[21][22][23][24][25][26][27][28][29][30][31][32][33]. Nicotine has also been shown to slow gastric emptying [13,34,35].…”
Section: Introductionmentioning
confidence: 99%